Strategic insights from a Delphi study: enhancing employment for multiply marginalized people with disabilities - Goddard, Kelsey S.; Kurth, Noelle K.; Hall, Jean P.; Koon, Lyndsie M.; Moore, Corey L.; Dentleegrand, Kacie R. (Frontiers in Rehabilitation Sciences, 2024)
IntroductionThe employment landscape for multiply marginalized people with disabilities presents significant challenges, exacerbated by intersecting identities such as race/ethnicity, sexual orientation, gender identity, poverty, and geography. Recent studies highlight the compounded employment disparities faced by this group, including discriminatory hiring practices, inadequate accommodations, and uneven gains in employment during the COVID-19 public health emergency.MethodsOur study employed a three-round Delphi process with 20 diverse experts across 14 states across the United States (U.S.) to formulate recommendations for improving employment experiences for multiply marginalized people with disabilities. The panel's insights were gathered through surveys administered online, with each round designed to refine the collective recommendations. This iterative process aimed to build a consensus on the most effective policy and practice recommendations for improving employment outcomes within this population.ResultsThe Delphi study identified key areas for strategic focus, including emergency preparedness, education and training, transportation, assistive technology, workplace accommodations, and combating discrimination and stigma. Notable recommendations included improving emergency preparedness training, enhancing employment education, increasing funding for accessible transportation and assistive technology, and promoting inclusive hiring practices. The study also emphasized the need for policies supporting telework and simplifying disability-related benefits.DiscussionThe findings highlight the critical role of tailored strategies to address employment challenges faced by people with disabilities from marginalized communities. Meaningfully and fully implementing these recommendations would create a more inclusive environment that improves employment outcomes for multiply marginalized people with disabilities.